Efektivitas Konseling Kelompok melalui Teknik Acceptance and Commitment Theraphy dalam Meningkatkan Self Efficacy Mahasiswa - Vinda Chairunnisa; Ika Sandra Dewi (Education & Learning, 2026)
Self-efficacy is an important psychological factor that influences students' ability to cope with academic demands and psychosocial pressures in higher education. Low self-efficacy can impact on decreased learning motivation, psychological resilience, and general student well-being. This study aims to test the effectiveness of group counseling with Acceptance and Commitment Therapy (ACT) techniques in improving student self-efficacy. This study used a quantitative approach with a quasi-experimental design in the form of a non-equivalent control group design. The research subjects consisted of 10 students of the Guidance and Counseling Study Program of UMN-Al Washliyah Medan who had low levels of self-efficacy, who were divided into an experimental group (n=5) and a control group (n=5) through a purposive sampling technique. The experimental group was given an ACT-based group counseling intervention, while the control group was not given any treatment. Data collection was carried out through a self-efficacy scale at the pretest and posttest stages. Data analysis used the Wilcoxon Signed Ranks Test with a significance level of ? = 0.05. The results showed a significant increase in self-efficacy in the experimental group after the ACT intervention (p = 0.029), while the control group showed no significant change (p > 0.05). These findings indicate that group counseling using the ACT technique is effective in increasing student self-efficacy. Therefore, this approach can be recommended as an alternative intervention in guidance and counseling services in higher education to support the development of students' psychological capacity.